The impact of intellectual rent management on the development of sustainable education strategies in academic institutions: An exploratory study of the opinions of a sample of professors from Iraqi private universities. Assistant - Kashkool, Professor Dr. Hussein Mohammed Ali Kashkool; Al-Maliki, Professor Dr. Nidal Abdullah Al-Maliki; Ali, Assistant Instructor Ghazi Faisal Mohammed Ali (Sulaimani Journal for Humanities, 2026)
This study aims to explore the impact of intellectual rent management on the development of sustainable education strategies in academic institutions. This study was conducted within the framework of a survey of the opinions of professors from Iraqi private universities, which included three universities: Warith Al-Anbiya University, Al-Bayan University, and Al-Zahra University. The colleges of administration and economics, education, and arts were selected in these universities, where a sample of 218 professors were selected from these colleges. The study focused on how intellectual rent management affects the improvement and enhancement of sustainable education strategies within these academic institutions. The data extracted from the questionnaires distributed to professors were analyzed, with a focus on understanding the impact of knowledge management, intellectual innovation, and intellectual property protection on the development of a sustainable educational environment. The results showed that there is a positive relationship between intellectual rent management and the development of sustainable education strategies. The study also emphasized the importance of stimulating knowledge innovation and promoting a culture of intellectual property rights within academic institutions in order to improve the sustainability of education. The professors indicated the need to adopt effective mechanisms to manage intellectual rent in a way that contributes to enhancing sustainable development and achieving societal benefit from academic knowledge. The study recommends the need to increase attention to intellectual rent management at the level of academic institutions by intensifying training programs for professors and organizing workshops to raise awareness about the importance of effective management of knowledge and intellectual property rights in promoting sustainable education.
Keywords: Intellectual rent management; sustainable education strategies; professors of Iraqi private universities